Using the general form a x 2 + b x y + c y 2 + d x + y = 0 , find the conic that goes thru the points ( 0 , 1 ) , ( 2 1 , 2 1 ) , ( 2 − 1 , 2 1 ) , ( 4 1 , 0 ) and ( 0 , 0 ) .
Find the parabola y = a x 2 + b x + c that goes thru the points ( 1 5 2 , 2 1 5 1 5 − 1 ) , ( 1 5 − 2 , 2 1 5 1 5 + 1 ) and ( 0 , 0 ) .
If the area A of the region bounded by the above conic(below the line y = 4 2 − x ) and the given parabola can be expressed as A = a b b c b π − a b , where a , b and c are coprime positive integers, find a + b + c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I just want to point out that for the first conic, the problem asks to put the conic in the form a x 2 + b x y + c y 2 + d x + y = − 1 . We are told that the conic passes through the point ( 0 , 0 ) , so plugging in x = 0 and y = 0 , we get 0 = − 1 . This means that the given form cannot work.
Log in to reply
I meant a x 2 + b x y + c y 2 + d x + y = 0 , but I assume that everyone(including yourself) that solved the problem realized that given the point ( 0 , 0 ) would have to mean that a x 2 + b x y + c y 2 + d x + y = 0 .
Problem Loading...
Note Loading...
Set Loading...
Let a x 2 + b x y + c y 2 + d x + y = 0
Using the points ( 0 , 1 ) , ( 2 1 , 2 1 ) , ( 2 − 1 , 2 1 ) , ( 4 1 , 0 ) and ( 0 , 0 ) we obtain the system:
a + b + c + 2 d + 2 = 0
a − b + c − 2 d + 2 = 0
c + 1 = 0
a + 4 d = 0
⟹ a + c + 2 = 0 , c = − 1 , a = − 4 d ⟹ d = 4 1 ⟹ a = − 1 and b = 2 − 1 ⟹ 4 x 2 + 2 x y + 4 y 2 − x − 4 y = 0 , since b 2 − 4 a c < 0 ⟹ the conic is an ellipse..
To find the area we need to solve for y obtaining:
y = 4 1 ( ± 4 − 1 5 x 2 − ( x − 2 ) )
We only need g ( x ) = 4 1 ( − 4 − 1 5 x 2 − ( x − 2 ) ) , which is the portion of the ellipse below the line y = 4 2 − x .
For the parabola y = a x 2 + b x + c that goes thru the points ( 1 5 2 , 2 1 5 1 5 − 1 ) , ( 1 5 − 2 , 2 1 5 1 5 + 1 ) and ( 0 , 0 ) we obtain:
c = 0
1 5 4 a + 1 5 2 b = 2 1 5 1 5 − 1
1 5 4 a − 1 5 2 b = 2 1 5 1 5 + 1
⟹ a = 8 1 5 and b = 4 − 1 ⟹ y = 8 1 5 x 2 − 2 x .
To find the points of intersection for the two curves let f ( x ) = g ( x ) ⟹ 2 x − 1 5 x 2 = 2 ( 4 − 1 5 x 2 + x − 2 ) ⟹ ( 4 − 1 5 x 2 ) 2 = 4 ( 4 − 1 5 x 2 ) ⟹
1 5 x 2 ( 1 5 x 2 − 4 ) = 0 ⟹ x = 0 , x = ± 1 5 2 .
The area A = ∫ 1 5 − 2 0 f ( x ) − g ( x ) d x + ∫ 0 1 5 − 2 f ( x ) − g ( x ) d x ) = 8 1 ∫ 1 5 − 2 1 5 2 1 5 x 2 − 2 x + 2 ( 4 − 1 5 x 2 + x − 2 ) d x
Letting 1 5 x = 2 sin ( θ ) ⟹ d x = 1 5 2 cos ( θ ) ⟹
A = 8 1 ( 1 5 4 π − 1 5 1 6 + 3 1 5 1 6 ) = 6 1 5 3 π − 8 = 2 ∗ 3 3 ∗ 5 3 π − 2 3 = a b b c b π − a b ⟹ a + b + c = 1 0 .